2019
DOI: 10.1038/s41598-019-55460-9
|View full text |Cite
|
Sign up to set email alerts
|

Nectin-4 cis-interacts with ErbB2 and its trastuzumab-resistant splice variants, enhancing their activation and DNA synthesis

Abstract: Nectin-4 cell adhesion molecule and ErbB2 tyrosine kinase receptor are upregulated in many cancers, including breast cancer, and promote cancer cell proliferation and metastasis. Using human breast cancer cell lines T47D and SUM190-PT, in which both nectin-4 and ErbB2 were upregulated, we showed here that nectin-4 cis-interacted with ErB2 and enhanced its dimerization and activation, followed by the activation of the phosphoinositide 3-kinase-AKT signalling pathway for DNA synthesis. The third immunoglobulin-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 64 publications
(97 reference statements)
0
32
1
Order By: Relevance
“…The SOX2 gene expression is induced by many signaling pathways including the PI3K-AKT signaling 45 49 . Detailed studies revealed here that nectin-4 and any one of p95-ErbB2, ErbB2, or ErbB2∆Ex16 cooperatively activated the PI3K-AKT signaling to similar extents 33 , but that only the combination of nectin-4 and p95-ErbB2, but not that of nectin-4 and either ErbB2 or ErbB2∆Ex16, cooperatively activated the Hippo signaling to regulate the SOX2 gene expression. In this signaling pathway, MST1/2 phosphorylates and activates LATS1/2, which in turn phosphorylates YAP, keeping the phosphorylated YAP in the cytoplasm, thus inhibiting its activity 50 .…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…The SOX2 gene expression is induced by many signaling pathways including the PI3K-AKT signaling 45 49 . Detailed studies revealed here that nectin-4 and any one of p95-ErbB2, ErbB2, or ErbB2∆Ex16 cooperatively activated the PI3K-AKT signaling to similar extents 33 , but that only the combination of nectin-4 and p95-ErbB2, but not that of nectin-4 and either ErbB2 or ErbB2∆Ex16, cooperatively activated the Hippo signaling to regulate the SOX2 gene expression. In this signaling pathway, MST1/2 phosphorylates and activates LATS1/2, which in turn phosphorylates YAP, keeping the phosphorylated YAP in the cytoplasm, thus inhibiting its activity 50 .…”
Section: Introductionmentioning
confidence: 78%
“…We further showed that nectin-4 also cis -interacts with the trastuzumab-resistant splice variants of ErbB2, p95-ErbB2 and ErbB2∆Ex16, activating the PI3K-AKT signaling and enhancing DNA synthesis 33 . In addition, nectin-4 activates the p95-ErbB2-induced JAK-STAT signaling, but not the ErbB2- or ErbB2∆Ex16-induced JAK-STAT signaling 33 .…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…Nectin cell adhesion molecule 4 is normally expressed in the epithelium of the bladder, epidermis of the skin, salivary glands (ducts), and mammary glands [16,22]. Interestingly, NECTIN4 is overexpressed in some epithelial cancers, and its overexpression is correlated with tumor progression and patient outcome [16,22,23,26]. However, the detailed expression of NECTIN4 in human skin and its role in skin tumors have not been examined.…”
Section: Introductionmentioning
confidence: 99%